NANOPARTICLE OF FAITH ON NURSES INTERVENTIONS - Paula Soares Encarnação; Clara Costa Oliveira; Teresa Martins; Clara Costa Oliveira (Reflexão & Ação, 2016)
The World Health Organization, in recent years has stimulated the development of research studies that have positive implications for the quality of people's health, such as spirituality. This topic discusses the concept of faith as an expression of human spirituality; develops the idea of faith as a “nanoparticle” that can be used in nursing care as an intervention to promote people’s health, and explore the contribution to education in Nursing. Given these findings it is concluded that nurses should require training and develop research studies that demonstrate faith as a protective factor and a health promoter with salutogenic effects in the Portuguese context.